Serine 220 phosphorylation of the Merkel cell polyomavirus large T antigen crucially supports growth of Merkel cell carcinoma cells. Issue 5 (5th October 2015) - Schrama, David; Hesbacher, Sonja; Angermeyer, Sabrina; Schlosser, Andreas; Haferkamp, Sebastian; Aue, Annemarie; Adam, Christian; Weber, Alexandra; Schmidt, Marc; Houben, Roland
Abstract : Merkel cell polyomavirus (MCPyV) is regarded as a major causal factor for Merkel cell carcinoma (MCC). Indeed, tumor cell growth of MCPyV‐positive MCC cells is dependent on the expression of a truncated viral Large T antigen (LT) with an intact retinoblastoma protein (RB)‐binding site. Here we determined the phosphorylation pattern of a truncated MCPyV‐LT characteristically for MCC by mass spectrometry revealing MCPyV‐LT as multi‐phospho‐protein phosphorylated at several serine and threonine residues. Remarkably, disruption of most of these phosphorylation sites did not affect its ability to rescue knockdown of endogenous T antigens in MCC cells indicating that phosphorylation of the respective amino acids is not essential for the growth promoting function of MCPyV‐LT. However, alteration of serine 220 to alanine completely abolished the ability of MCPyV‐LT to support proliferation of MCC cells. Conversely, mimicking the phosphorylated state by mutation of serine 220 to glutamic acid resulted in a fully functional LT. Moreover, MCPyV‐LT S220A demonstrated reduced binding to RB in co‐immunoprecipitation experiments as well as weaker induction of RB target genes in MCC cells. In conclusion, we provide evidence that phosphorylation of serine 220 is required for efficient RB inactivation in MCC and may therefore be a potential target for future therapeutic approaches. Abstract : What's new? To find possible points of attack, this study investigated the phosphorylation pattern of a viral protein that causes skin cancer. The large T antigen produced by Merkel cell polyomavirus contains a retinoblastoma protein binding site and drives tumor growth. These authors located several serine and threonine residues in the protein which become phosphorylated. Upon testing several variants, each containing a disruption in one of these phosphorylation sites, they found one, serine 220, which had lost the ability to bind RB and failed to promote cell proliferation. Disrupting this site, then, could halt the spread of Merkel cell carcinoma.